Respuesta :
The answer is: [A]: 3√ 2 .
______________________________
Explanation:
______________________________
Simply: -3√ 2 + 3√ 8 ;
_______________________________
Let us simplify: 3√ 8 ;
________________________________________________
Let us simplify:
________________________________________________
√ 8 ; → √ 8 = √ 4 * √ 2 = 2√ 2 ;
________________________________________________
→ √ 8 = √ 4 * √ 2 = 2√ 2 ;
__________________________________
→ 3√ 8 = 3 * 2√ 2 = 6√ 2 ;
____________________________________________________
So, rewrite the original problem, substituting: "6√ 2" for "3√ 8" ;
____________________________________________________
-3√ 2 + 3√ 8 =
____________________________________________________
-3√ 2 + 6√ 2 = 3√ 2 ; which is Answer choice: [A].
____________________________________________________
______________________________
Explanation:
______________________________
Simply: -3√ 2 + 3√ 8 ;
_______________________________
Let us simplify: 3√ 8 ;
________________________________________________
Let us simplify:
________________________________________________
√ 8 ; → √ 8 = √ 4 * √ 2 = 2√ 2 ;
________________________________________________
→ √ 8 = √ 4 * √ 2 = 2√ 2 ;
__________________________________
→ 3√ 8 = 3 * 2√ 2 = 6√ 2 ;
____________________________________________________
So, rewrite the original problem, substituting: "6√ 2" for "3√ 8" ;
____________________________________________________
-3√ 2 + 3√ 8 =
____________________________________________________
-3√ 2 + 6√ 2 = 3√ 2 ; which is Answer choice: [A].
____________________________________________________